A survey of manpower: Londonderry, Coleraine, Limavady and Strabane - a case study - Garmany, J. W. (Statistical and Social Inquiry Society of Ireland, 1964)
Measures aimed at levelling out regional disparities fall broadly into two groups, those operating on the labour market and geared towards greater flexibility, mobility and rehabilitation, and those designed to induce a more even and more stable spread of investment. At any time both are necessary but where the emphasis lies depends on the prevailing employment situation and on the objectives, whether the worker is to be brought to the job or the job to the worker.
Read before the Society, 27 January 1964
Keywords: Labour force; Labour productivity; Northern Ireland; 314.15